Towards practical cells: combined use of titanium black as a cathode additive and sparingly solvating electrolyte for high-energy-density lithium–sulfur batteries. Issue 6 (3rd March 2021) - Liu, Jiali; Li, Shanglin; Marium, Mayeesha; Wang, Binshen; Ueno, Kazuhide; Dokko, Kaoru; Watanabe, Masayoshi
Abstract : Combined use of titanium black as a cathode additive and sparingly solvating electrolyte is promising for practical lithium–sulfur batteries. Abstract : The lithium–sulfur (Li–S) battery is considered one of the most promising technologies for next-generation energy storage. To realise its practical applications, electrodes with high areal sulfur loading, low-cost raw materials, and easily accessible fabrication processes are essential. Herein, we demonstrated the effectiveness of a commercially available black pigment, titanium black (TiB), as a multi-functional additive for sulfur electrodes. Benefiting from the amphipathic nature of TiB, it was easy to obtain a homogenous coating on a current collector (>4 mg cm −2 ) by applying a traditional slurry containing aqueous carboxymethyl cellulose/styrene-butadiene rubber as a binder. Contact angle measurements revealed much better electrolyte wettability for the electrode with the addition of TiB. Combined with a sparingly solvating electrolyte based on sulfolane and Li[N(SO2 CF3 )2 ], the electrode showed excellent cycling performance and high coulombic efficiency at a relatively high current density. Finally, pouch cells were fabricated with a low electrolyte/sulfur (E/S) ratio of 3.2 μL mg −1, and a high energy density of 280 W h kg −1 was achieved. Subsequent investigation of the gassing behaviour revealed that swelling of the charged cells at 60 °C was suppressed for half a month. This study may pave the way for designing Li–S batteries with practical utility.